Evaluation of physicochemical/microbial properties and life cycle assessment (LCA) of PLA-based nanocomposite active packaging. (January 2017) - Lorite, Gabriela S.; Rocha, João M.; Miilumäki, Noora; Saavalainen, Paula; Selkälä, Tuula; Morales-Cid, Gabriel; Gonçalves, M.P.; Pongrácz, Eva; Rocha, Cristina M.R.; Toth, Geza
Abstract: To attend the growing consumer demand for novel ready-to-eat fresh cut fruits packaging polylactic acid (PLA)-based active packaging was realized. The aim of these packaging is to provide an improved protection and even to extend their shelf-life. PLA-based active packaging was prepared by adding nanoclays and surfactants in its formulation. The evaluation of PLA-nanocomposite packaging was done in comparison to pristine PLA and conventional plastic (polyethylene terephthalate, PET) using fresh-cut melons. Physicochemical properties were investigated by the means of weight loss, visual appearance, pH, colour, and firmness. In addition, microbial profile was tested via microbiological assays. In order to evaluate the environmental impact of PLA-based active packaging compared to commonly used PET, life cycle assessment (LCA) was conducted. In terms of physicochemical and antimicrobial properties, the results clearly showed that the presence of nanoclays and surfactants in the PLA formulations improved their performance, thus contributing to bring the characteristic and behaviour of PLA packages close to those of PET. Furthermore, assessment of life cycle environmental impacts indicated that PLA packaging with nanoclays had the highest environmental performance. Highlights: We present a PLA-based nanocomposite active packaging for ready-to-eat fresh fruits packaging. We demonstrate an improved protection and even extended shelf-life. Behaviour of PLA packages are close to those of PET. Extensive life cycle assessment was performed.